Tobacco products and sensory health: An assessment of taste and smell disorders using 2021 NHIS data - Rahaf H. Bin Hamdan; Waad R. AlAmri; Muath A. Aldosari (Tobacco Induced Diseases, 2024)
Introduction This study aims to assess the relationship between use of tobacco products and taste and smell disorders.